Zinc transporter 8 autoantibody in the diagnosis of type 1 diabetes in children - Nur Rochmah, - (Korean Pediatric Society, 2020)
Background: Type 1 diabetes (T1D) is an organ-specific autoimmune disease related to the autoimmune response against pancreatic β-cells. Zinc transporter 8 (ZnT8), an islet-specific gene product localized to the β-cell insulin granule, was recently identified as an autoantigen in T1D. Purpose: To evaluate the use of ZnT8 autoantibody (ZnT8A) for diagnosing T1D. Methods: This case-control study was conducted at Dr. Soetomo General Hospital, Surabaya, Indonesia, from March to May 2019. Children younger than 18 years of age with T1D based on the International Society for Pediatric and Adolescent Diabetes guideline and healthy controls were included. We measured ZnT8A level using enzyme-linked immunosorbent assay (cutoff value, 0.315). Results: There were 30 children with T1D (50.0% boys; mean age, 11.3±3.7 years) and 18 healthy controls (44.4% boys; mean age, 8.3±3.1 years); 1 patient in each group was Madurese, while the others were Javanese. Twenty-two of 30 subjects with T1D (73.3%) tested positive for ZnT8A compared to 5 of 18 controls (27.8%) (P=0.02; odds ratio, 7.15; 95% confidence interval, 1.93–26.52). When ZnT8A-positive and -negative T1D cases were compared, no differences were detected in age at diagnosis, duration of diabetes, presence of ketoacidosis, body mass index, glycosylated hemoglobin concentration, or C-peptide concentrations. Conclusion: ZnT8A may be useful in the diagnosis of T1D.